Intensive Care Unit Admission Following Surgery for Pediatric Spinal Deformity: An Analysis of the ACS-NSQIP Pediatric Spinal Fusion Procedure Targeted Dataset. Issue 2 (April 2020) - Malik, Azeem Tariq; Yu, Elizabeth; Kim, Jeffery; Khan, Safdar N.
Study Design: Retrospective cohort. Objective: To understand which patient and surgical factors are predictive of an increased odds of undergoing an admission and a prolonged stay >2 days in an intensive care unit (ICU) following corrective surgery for pediatric deformity. Methods: The 2016 American College of Surgeons–National Surgical Quality Improvement Program (ACS-NSQIP) Pediatric Spinal Fusion Procedure Targeted database records, merged with original 2016 ACS-NSQIP Pediatric file variables, were used for this study. Univariate and multivariate analyses were used to identify independent risk factors associated with admission, as well as a prolonged length of stay in the ICU following surgery. Results: A total of 1398 (39.5%) patients required an ICU admission following the procedure—out of whom 416 (29.8%) stayed for more than 2 days. Following adjusted analysis, patient and surgical factors independently associated with an ICU admission were black/African American versus white race, anterior fusion, combined fusion, nonidiopathic scoliosis, preoperative ventilator dependence, asthma, having structural pulmonary abnormality, developmental delay, having a neuromuscular disorder, requiring nutritional support and a total operative time >270 minutes. The only significant factors associated with a prolonged length of ICU stay >2 days were preoperative ventilator dependence, nutritional support requirement, and undergoing anterior or combined fusion. Conclusions: This study is the first of its kind to identify significant patient- and procedure-level factors associated with an ICU admission, and also explores predictors for a prolonged stay in the ICU. Surgeons can use this data to preoperatively counsel families and ensure postoperative course of care is appropriately planned ahead of time.